Interpreting Legal Language at the International Criminal Tribunal for the Former Yugoslavia: overcoming the lack of lexical equivalents - Stern, Ludmila (The Journal of Specialised Translation, 2004)
This article explores difficulties experienced by court interpreters and the strategies they adopted in dealing with legal deliberations at the International Criminal tribunal for the Former Yugoslavia (ICTY). After giving an outline of interpreting practices at ICTY, the author considers interpreting approaches used in this context. Problems created by the use and transfer of cognates, synonyms and neologisms in legal language are highlighted. The author shows why paraphrasing and other techniques of explicitation are often the most effective in an international legal context.